2014
DOI: 10.1590/1809-9823.2014.13065
|View full text |Cite
|
Sign up to set email alerts
|

Alterações das funções de mastigação e deglutição no processo de alimentação de idosos institucionalizados

Abstract: ResumoObjetivo: Analisar o processo de alimentação de idosos institucionalizados e, mais especificamente, descrever o perfil sociodemográfico dos idosos, verificar as possíveis alterações estruturais do sistema estomatognático, das funções de mastigação e deglutição e constatar as dificuldades alimentares autorreferidas. Método: Estudo do tipo quantitativo, descritivo, observacional, transversal e prospectivo. A amostra foi constituída por 27 indivíduos do gênero feminino e três do gênero masculino, com idades… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0
28

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 9 publications
5
20
0
28
Order By: Relevance
“…Many physiological and psychosocial changes which impact the quality and quantity of food intake occur during the aging process. The most common are related to changes in peripheral hormones, control of the central nervous system and the organs directly involved in digestion, such as slow gastric emptying, xerostomia and reduced sensitivity of the senses, such as the palate 5,14 . Depression, mood disorders, loneliness, widowhood, lack of social support, isolation and poverty complete the factors that must be considered in the holistic approach of this population 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many physiological and psychosocial changes which impact the quality and quantity of food intake occur during the aging process. The most common are related to changes in peripheral hormones, control of the central nervous system and the organs directly involved in digestion, such as slow gastric emptying, xerostomia and reduced sensitivity of the senses, such as the palate 5,14 . Depression, mood disorders, loneliness, widowhood, lack of social support, isolation and poverty complete the factors that must be considered in the holistic approach of this population 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Healthy dietary patterns characterized by increased intakes of fruits and vegetables have been linked to lower risks of cancer, diabetes, cardiovascular disease and Alzheimer's disease, while Western dietary patterns (sugar, fat, processed foods and refined grains) may have the opposite effect. Studies have indicated that dietary patterns can be influenced not only by age, but also by gender, socioeconomic status, marital status, household arrangement, lifestyle and clinical conditions such as disease and mastigation [12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…The mobility, tone and function of this system's structures have direct influence in the masticatory process; even the aging process of these structures impair the ability to control the bolus and to correctly perform the chewing steps. These steps are related with the chewing and swallowing intrinsic and extrinsic muscles that, added with maladaptation of dental prosthesis, intensify the difficulties (17) .…”
Section: Discussionmentioning
confidence: 99%
“…Contudo, esse predomínio deve-se ao fato de terem sido excluídos seis indivíduos do sexo feminino (MENEZES; BACHION, 2008;GUTIERREZ et al, 2009;LÓPEZ et al, 2012;OLIVEIRA;DELGADO;BRESCO-VICI, 2014).…”
Section: Discussionunclassified